2019
DOI: 10.1016/j.neuropharm.2018.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to WIN55,212-2 is delayed in desensitization-resistant S426A/S430A mice

Abstract: Tolerance to cannabinoid agonists can develop through desensitization of the cannabinoid receptor 1 (CB 1 ) following prolonged administration. Desensitization results from phosphorylation of CB 1 by a G protein-coupled receptor kinase (GRK), and subsequent association of the receptor with arrestin. Mice expressing a mutant form of CB 1 , in which the serine residues at two putative phosphorylation sites necessary for desensitization have been replaced by non-phosphorylatable alanines (S426A/S430A), display re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…However, WT and GASP1 knockout mice both developed tolerance to WIN55,21202-mediated hypothermia, potentially due to differences in overlapping expression of CB1R and GASP1 in different brain regions driving diverse mechanisms of tolerance (Martini et al, 2010). However, one limitation of this study when extrapolating the results habitual cannabis users is the use of WIN55,212-2 rather than 9 -THC since desensitization, internalization, recycling, and tolerance are highly agonistspecific (Hsieh et al, 1999;Wu et al, 2008;Martini et al, 2007;Morgan et al, 2014;Nealon et al, 2019). Indeed, a recent study reported that 9 -THC-but not WIN55,212-2mediated tolerance is dependent on c-Jun N-terminal Kinase (JNK) signaling (Henderson-Redmond et al, 2020).…”
Section: G Protein-coupled Receptor Associated Protein 1 (Gasp1)mentioning
confidence: 92%
See 1 more Smart Citation
“…However, WT and GASP1 knockout mice both developed tolerance to WIN55,21202-mediated hypothermia, potentially due to differences in overlapping expression of CB1R and GASP1 in different brain regions driving diverse mechanisms of tolerance (Martini et al, 2010). However, one limitation of this study when extrapolating the results habitual cannabis users is the use of WIN55,212-2 rather than 9 -THC since desensitization, internalization, recycling, and tolerance are highly agonistspecific (Hsieh et al, 1999;Wu et al, 2008;Martini et al, 2007;Morgan et al, 2014;Nealon et al, 2019). Indeed, a recent study reported that 9 -THC-but not WIN55,212-2mediated tolerance is dependent on c-Jun N-terminal Kinase (JNK) signaling (Henderson-Redmond et al, 2020).…”
Section: G Protein-coupled Receptor Associated Protein 1 (Gasp1)mentioning
confidence: 92%
“…CB1R desensitization involves GPCR kinase 2/3 (GRK2/3)-mediated phosphorylation of two serine residues (S426 and S430), which recruit β-arrestin 1/2 and prevent G protein coupling (Jin et al, 1999;Kouznetsova et al, 2002;Daigle et al, 2008a;Morgan et al, 2014). Similar to deletion of β-arrestin 2, S426A/S430A knock in mice display reduced tolerance to cannabinoid-mediated pain for some agonists, but not others (Morgan et al, 2014;Nealon et al, 2019).…”
Section: Proteins That Interact With Ctcb1rmentioning
confidence: 99%
“…Like many other GPCRs, the CB receptors can also activate signaling through the beta-arrestin protein (Breivogel et al, 2013;Priestley et al, 2017;Tonini et al, 2006). This signaling pathway has been implicated in control of cell surface receptor turnover via mechanisms involving CB1 phosphorylation by a G proteincoupled receptor kinase (GRK) (Jin et al, 1999;Morgan et al, 2014;Nealon et al, 2019;Nguyen et al, 2012). Through these signaling pathways CB receptors can influence a variety of cellular processes, including neurophysiology, membrane protein trafficking and gene expression (Sim-Selley, 2003).…”
Section: Thc and Cannabinoid Receptorsmentioning
confidence: 99%
“…It is unclear how CNS penetrance of CB-13 would lead to anti-allodynic tolerance, as the anti-allodynia caused by CB-13 was shown to be peripheral CB 1 -mediated acutely. One interpretation may be that functional CB 1 desensitization in the central tissues renders peripheral CB 1 activation to become no longer effective as witnessed with other centrally penetrant cannabinoid agonists [18,19,40,50,54,71] and upregulation of 2arachidonoylglycerol via monoacylglycerol lipase inhibition [14,39,65]. Further work is needed to better understand the mechanisms underlying anti-allodynic tolerance following repeated activation of CB 1 receptors.…”
Section: Discussionmentioning
confidence: 99%